Unequal partners : power relations, devolution and development in Uttar Pradesh - Lieten, G. K. (Georges Kristoffel), 1946-; Srivastava, Ravi, 1953- (London : Sage, 1999)
"This book takes the contemporary discussion on devolution of power to the local level (the panchayats) as the point of entry for a discussion of various aspects of village life in Uttar Pradesh."--BOOK JACKET. "This in-depth view from below is an enriching insight into the resilience and dynamism of social life in the villages of north India. It will interest those involved in village studies, and in the fields of political science, economics, rural development, public administration and sociology."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Rural development -- India -- Uttar Pradesh; Decentralization in government -- India -- Uttar Pradesh